Auditorium (later Old Meany Hall), University of Washington, between 1909 and 1911 (1909)
Caption on postcard: Auditorium. University of Wash. Handwritten on verso: Feb 10, 1911 Filed in: UW - Buildings - Meany Hall (Old) The Auditorium Building was built for the 1909 Alaska-Yukon-Pacific Exposition where it was used for concerts, speeches and other gatherings. In 1914 after the Exposition, the building was renamed Meany Hall, thanks to a campaign led by The Daily (UW’s student newspaper) to honor Professor Edmund S. Meany. From 1909 to 1965, Meany had the largest capacity of any building on campus with 2,600 seats. It was demolished in 1965 after suffering earthquake damage. In 1995, the Allen Center for the Visual Arts was erected in Meany Hall’s former location.